2016
DOI: 10.1177/0309324716663940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elasto-plastic material behaviour on determination of residual stress profiles using the hole drilling method

Abstract: The hole drilling method is a well-known technique for the determination of non-uniform residual stress profiles by measuring relaxation distortions caused by the presence of the hole. The integral method, an inverse calculation technique on which the hole drilling method is based, assumes linear elastic material behaviour and is therefore limited to the measurement of residual stresses below 60% of the yield strength. The aim of this study is to investigate the effects of elastic-plastic material behaviour on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…This residual stress state can be caused by the rolling process of the sheet material. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 overestimates the residual stress values when they are close to the yield strength of the material, as investigated by Chupakhin et al (2015) [2], the actual residual stress values should be lower. Nevertheless, the hole drilling technique provides a useable qualitative result.…”
Section: Figure 2 Crystal Orientation Maps and Inverse Pole Figures mentioning
confidence: 85%
“…This residual stress state can be caused by the rolling process of the sheet material. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 overestimates the residual stress values when they are close to the yield strength of the material, as investigated by Chupakhin et al (2015) [2], the actual residual stress values should be lower. Nevertheless, the hole drilling technique provides a useable qualitative result.…”
Section: Figure 2 Crystal Orientation Maps and Inverse Pole Figures mentioning
confidence: 85%
“…500 MPa are significantly higher than the yield strength of the material investigated (370 MPa). As the used hole drilling technique overestimates residual stress values close or above the yield strength of the material, as investigated in [13], the real residual stress values should be lower. In case of equibiaxial residual stress profiles a correction methodology based on artificial neural network can be applied [14].…”
Section: Residual Stress Analysismentioning
confidence: 96%
“…Beghini et al, with consideration to the local plasticity induced by the introduction of the hole, showed plasticity‐induced errors of around 40% and proposed a procedure to take into account its effects on the residual stress evaluation. Lately, Chupakhin et al showed significant overestimated plasticity‐induced errors in the case where the residual stresses exceeded from 60% of the yield strength. They also provided an indication of the range of depth, at which the residual stress profile should be corrected.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Thus, in view of this, an incremental milling of a circular groove on a stressed plate was simulated using the killing element technique. Residual stresses were simulated by applying mechanical uniform preloading on a plate before the ring‐core milling, as in the past researches on the hole‐drilling and ring‐core techniques . Strain due to preloading and ring milling was sensed by the three resistance strain gauges located in the principal directions on the specimen.…”
Section: Finite Element Analysismentioning
confidence: 99%
See 1 more Smart Citation